Exploring the relationship between learning approaches and problem-based learning: insights from a longitudinal study in medical students - D Avraam; I Televantou; AP Albert; AW Hitchings; SA Nicolaou; A Papageorgiou; P McCrorie; P Nicolaou (BMC Medical Education)
Abstract Background Problem-based learning (PBL) is expected to encourage a deep learning approach. Whether this is realised in practice remains uncertain. We investigated the relationships between learning approaches, academic achievement and student satisfaction in an integrated PBL curriculum, among students with diverse characteristics. Methods All Year 1 students of an undergraduate UK medical programme, delivered concurrently at City St George’s, University of London and the University of Nicosia, were invited to participate in 2019–2020 and 2020–2021. Students completed the validated Study Process Questionnaire (SPQ) at the beginning and end of Year 1. We explored changes in learning approaches and the associations of the learning approach with academic performance (in written and clinical examinations) and student satisfaction. Results 129 students participated. Deep motivation decreased significantly over the year [Baseline: 11.03 ± 2.29; End of Year 1: 10.21 ± 2.26; p < 0.05). Graphical representations and tertile analysis further showed changes in individual learning approaches. Lower deep motivation scores were observed among male students, and those who were older, white, held biomedical sciences degrees, undergraduate degrees, or were native English speakers. Conversely, higher surface motivation was seen among female students, and those who were younger or held undergraduate degrees. Nicosia students became less strategic by the end of the year. No association was found between learning approach, or its change within the year, and examination performance. However, surface learning was negatively correlated with satisfaction regarding aspects of pharmacology learning in PBL and prescribing confidence. Strategic learners preferred lectures and had mixed perceptions about learning pharmacology in PBL, although they found student diversity facilitated their learning. Conclusions While PBL is expected to promote deep learning, our findings show that in a real-world context, these benefits are not consistently realised. Learners adopted less favourable learning approaches over the year, with increasing reliance on surface learning and less deep motivation. Such shifts may be due to excessive workload, assessment burden or curriculum uncertainty. We have identified student groups that may be more vulnerable to the stresses of a PBL setting, which may represent targets for intervention. Future studies may also investigate curriculum adaptations to enhance deep learning in a PBL curriculum.